2002
DOI: 10.1097/00003246-200201000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of gastric intraluminal carbon dioxide pressure, cardiac output, and end-tidal carbon dioxide pressure in the perioperative period in patients receiving cardiovascular surgery using cardiopulmonary bypass

Abstract: PgCO2 changed independently of CCO, and its postoperative elevation was related to morbidity, even in the group of patients with a good outcome. Continuous monitoring of PgCO2 is useful for the detection of morbidity and can be expected to help elucidate the pathophysiology of change of PgCO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…However, differences in transurgical PCO 2 gap values had no predictive value of postoperative outcome. In agreement with the data reported by Imai et al (2002), the PCO 2 gap changes during the first ICU hour correlated with postoperative morbidity although in the present study the differences did not reach statistical significance. In addition, gastric impedance parameters showed higher sensitivity than other global pressure-related variables used in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, differences in transurgical PCO 2 gap values had no predictive value of postoperative outcome. In agreement with the data reported by Imai et al (2002), the PCO 2 gap changes during the first ICU hour correlated with postoperative morbidity although in the present study the differences did not reach statistical significance. In addition, gastric impedance parameters showed higher sensitivity than other global pressure-related variables used in clinical practice.…”
Section: Discussionsupporting
confidence: 91%
“…Several new technologies are currently under development; however, to date no useful method to directly monitor the level of end organ tissue injury is available in clinical practice. Gastric tonometry (Bohrer et al 1997, Bennett-Guerrero et al 2000, Janssens et al 2000, Perez et al 2000, Imai et al 2002, regional capnometry (Lebuffe et al 1999), esophageal doppler ultrasonography (Poeze et al 1999), and more recently, near infrared spectroscopy (NIRS) (Uilkema and Groeneveld 2007) have been used to monitor end-organ perfusion in cardiac surgery patients. Nevertheless, these monitoring techniques do not give an estimate of the level of tissue compromise after prolonged ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Conjunctival carbon dioxide tension did change significantly during testing. One study of gastric luminal PCO 2 during CPB demonstrated declining values initially, and, similar to our findings, an increase upon the restoration of pulsatile flow (18). These authors attributed this finding to the increasing acidosis in tissues that are not perfused.…”
Section: Discussionsupporting
confidence: 89%
“…A prior investigation which measured muscle gastric mucosal oxygen levels during JECT. 2011;43: [13][14][15][16][17][18] CPB showed that tissue oxygenation fell sharply during the initiation of cardiopulmonary bypass and remained significantly below baseline for 3 to 5 hours following the procedure (19). These investigators did not find any relationship between arterial blood gas levels and the tissue pH or oxygen tension.…”
Section: Discussionmentioning
confidence: 98%